A comprehensive review of research progress on the genus Arisaema: Botany, uses, phytochemistry, pharmacology, toxicity and pharmacokinetics. (1st March 2022) - Su, Fazhi; Sun, Yanping; Zhu, Wenbo; Bai, Chenxi; Zhang, Wensen; Luo, Yumeng; Yang, Bingyou; Kuang, Haixue; Wang, Qiuhong
Abstract: Ethnopharmacological relevance: The genus Arisaema belongs to the family Araceae, which includes Chinese herbal medicines with wide-ranging pharmacological functions, including those useful for the treatment of stubborn phlegm, cough, epilepsy, tetanus, snakebite, rheumatoid arthritis, and other ailments. Aim of the study: The current study aimed to comprehensively review the botany, uses, phytochemistry, pharmacology, toxicity, quality control and pharmacokinetics of plants in the genus Arisaema and to provide novel insights to develop future research in this field. Materials and methods: Relevant information on the genus Arisaema was obtained from published scientific materials (including materials from PubMed, Elsevier, Web of Science, Google Scholar, Baidu Scholar, CNKI, and Wiley) and other literature sources (e.g., the Chinese Pharmacopoeia, 2020 edition; Chinese herbal books and PhD and MSc thesis). Results: The application information complied with this review and included processing techniques, traditional uses, clinical applications and classic prescriptions. Approximately 260 compounds, including flavonoids, alkaloids, saccharides, steroids, fatty acids, amino acids and volatile oils, have been separated and identified from the genus Arisaema . The isolated compounds exhibit wide-ranging pharmacological activities such as antitumor activity, analgesic and sedative activity, antioxidant activity and anti-inflammatory activity. The toxicity and irritant impacts, quality control, and pharmacokinetics are also discussed in this review. Conclusions: Plants in the genus Arisaema are valuable resources with therapeutic potential for a broad spectrum of ailments. Based on the limited literature, this review comprehensively and systematically summarizes current knowledge regarding the genus Arisaema for the first time. However, there have been insufficient studies on the active ingredients and germplasm and insufficient in-depth mechanistic studies. Therefore, isolation and identification of additional effective components and through research on the germplasm, pharmacodynamic mechanisms, and toxicology should be conducted to assess effectiveness and safety and to ensure the quality of the related drugs. Graphical abstract: Image 1